Africa and Insecurity: The Role of Philosophy towards Resolving Security Issues in Africa - Adekiitan, Omotayo; Falana, Christiana Titi (Universitas Negeri Makassar, 2021)
Security is essential for the survival and flourishing of any society. It involves the protection of individuals, communities, and nations against dangers and attacks. Security is so important that every government spends a substantial part of its money on its provision. Every community is only as strong or weak as the state of its security. This paper is a critical appraisal of security issues in Africa. Many African countries encounter security problems daily. Some of the challenges include -Islamist militancy by groups like al- Shabaab and Boko Haram, socio-political instability, xenophobic attacks, kidnappings, ritual killings, banditry, human trafficking, gender-based violence, and cybercrimes. Weak institutions, corruption, poverty, and marginalisation – political, economic, and social, are some of the fundamental roots of insecurity in Africa. The spate of insecurity in African nations calls for deep concern and concerted efforts to stem the tide. Moreover because in today’s world, insecurity anywhere is a threat to security everywhere; terrorism across the continent has led to mass displacements of families and individuals. Insecurity of lives and properties has reached alarming levels in places like Nigeria and Somalia at the moment. The present coronavirus pandemic also constitutes a threat to the security of lives in African nations such as South Africa, Algeria, Nigeria, Cameroon, Sudan, and the world at large. The article seeks to assess the current state of security in the African continent, examine the immediate and remote causes of insecurity and attempt solutions to the problem. The paper adopts conceptual analysis and reflective methods and maintains that Philosophy has an important role to play in resolving the insecurity issues in African societies.